Near field measurement technique - Law, Choi Look (2008)
Antenna measurements are widely used for a number of research projects as well as student projects. The range of antenna under test for such projects covers broad frequency ranges and antenna sizes. An anechoic chamber and antenna measurement equipment are acquired through an earlier AcRF project. This allow for accurate measurements of antenna patterns in a controlled environment. In this research project the objectives are (i) to establish the measurement accuracy of the Planar NF Test Range at L, S, C, X and Ku Bands (ii) to establish the accuracy of the NF Test Range for Broad Beam Antenna Pattern Measurement and (iii) to investigate the parameters that affect the measurement accuracy, e.g. the distance between the scanning probe and the Antenna-Under-Test (AUT). The work consisted of a series of self-tests, theoretical derivation, HFSS simulation, near field measurement and far-field pattern comparisons.